Beggar your neighbour (or why you do want to pay your taxes) - Munoz-Darde, V; Martin, M (Oxford University Press, 2018)
This paper looks at moral justifications for funding welfare benefits through general taxation rather than seeking to support it through charitable giving. That is, the parties to the debate are assumed to accept the moral imperative to support the destitute, and the political question is whether there is any requirement to do so through taxation. The chapter explores parallels between begging and the raising of charitable donations, highlighting not only the costs of begging on supplicants, but those that fall as well on the would-be donors. In the light of this, the chapter offers a justification for using taxation as a preferred way of raising resources for the provision of welfare benefits which has echoes of, but contrasts with, a famous proposal by Thomas Nagel.